2005
DOI: 10.1542/peds.2004-2680
|View full text |Cite
|
Sign up to set email alerts
|

The Pediatrician’s Role in Community Pediatrics

Abstract: ABSTRACT. This policy statement reaffirms the pediatrician's role in community pediatrics. It offers pediatricians a definition of community pediatrics and provides a set of specific recommendations that underscore the critical nature of this important dimension of the profession. Pediatrics 2005;115:1092-1094; community, pediatrics, pediatrician, role of, definition of, profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…A recent study by Ariza et al [98] demonstrated the feasibility of identifying overweight children in pediatric practices and then linking families to existing community-based programs. Linking children and families to community resources is a practice in line with American Academy of Pediatrics recommendations for pediatricians, which highlight the importance of pediatrician community connectedness in the prevention and treatment of public health issues, such as obesity [99, 100]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Ariza et al [98] demonstrated the feasibility of identifying overweight children in pediatric practices and then linking families to existing community-based programs. Linking children and families to community resources is a practice in line with American Academy of Pediatrics recommendations for pediatricians, which highlight the importance of pediatrician community connectedness in the prevention and treatment of public health issues, such as obesity [99, 100]. …”
Section: Discussionmentioning
confidence: 99%
“…Many providers agree that the recommendations of the American Academy of Pediatrics for screening of caregivers’ psychosocial needs and families’ social and economic needs are valuable, but many clinicians do not do so. 55,56 Pediatricians could screen for maternal depression, as one relevant health outcome, but feasible practices for assessment and care are relatively untested. 57 As another strategy, family medical homes are comprehensive medical care facilities that intend to address child, youth, and adult care needs concomitantly, recognizing family context.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, specific subspeciality 'community paediatricians' exist and have a unique opportunity to develop and foster interagency relationships in schools and communities; with a holistic vision and a preventative orientation [39]. In the USA, the American Academy of Pediatrics (AAP) has emphasised the importance of the paediatrician's role to advocate for children, collaborate with other professionals and provide health care with the context of a community [40]. It would appear that Lucy may have Table 1…”
Section: Relationships Between Professionalsmentioning
confidence: 99%